Prevalence and death rate of COVID-19 in some selected countries and its socio-economic impacts in Khulna division of Bangladesh - Sohidullah, M.; Khan, Shahidur R.; Alam, Ashiqul; Rahman, Nahid; Kundu, Swarup K.; Rahman, Arifur (International Journal Of Community Medicine And Public Health, 2021)
Background: 2019-nCoV has been declared by WHO as a global pandemic in March 2020. The present study was undertaken to find out the global as well as local prevalence, and death rate of COVID-19. Methods: A developed questionnaire was used in Khulna division of Bangladesh to record the percentages of people who were mask user, involved with different risk groups, harmed by socio-economic impacts of COVID-19, involved with the issue of government taking measures for controlling COVID-19. Some of the highly risk countries of the world were selected for recording the data. Results: As of October 20, 2020, we found USA, and Bangladesh at 1st and 17th position respectively in terms of global prevalence of COVID-19. We found Dhaka at 1st position in terms of division wise prevalence in Bangladesh. In terms of death rate of COVID-19, Mexico reported 10.10% death rate by securing 1st position. We recorded the data related with percentages of people who were involved with mask using and risk groups like hypertension, diabetes, respiratory illness, smoking; harmed by socio-economic impacts of COVID-19 that changed their lives, believers of different levels on government taking measures for controlling the spread of COVID-19 from Khulna division. Conclusions: The findings of this research work would certainly help the government of highly risk countries as well as Bangladesh to take appropriate measures to control COVID-19. Moreover, it will be helpful for the government of Bangladesh to take necessary steps to mitigate the socio-economic crises existing among the people.